Bio-Active Products from Mangrove Ecosystems (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Mangrove communities represent a coastal habitat located in the intertidal zone or brackish water of tropical and subtropical coastal areas, between 5°N and 5°S latitudes, spanning over 118 countries. The special ecological conditions of mangroves include high salinity, nutrient limitation, tidal gradients, high temperatures, excessively high light, and muddy anaerobic or sandy soil, which lead to various morphological and physiological adaptations of inhabiting species and act as an effective selector for the metabolic pathway via the generation of unique functional metabolites with highly unique chemical scaffolds and pharmaceutical application potential. In recent decades, numerous metabolites with uncommon structures and efficacious bioactivities have been discovered in mangrove-derived microorganisms, along with mangrove plants. For this reason, mangrove ecosystems have taken the limelight as an attractive biodiversity hotspot, attracting significant attention from organic chemists and pharmacologists. Additionally, many unique and novel chemical structures with a wide range of structural classes have suggested various biosynthetic origins containing novel functional genes and corresponding enzymes with unique catalytic functions. In this Special Issue, we welcome articles describing recent studies and pertinent reviews focusing on the latest and most important developments in bioactive product discovery from mangrove ecosystems and correlating structures with chemical synthesis, biosynthesis, genomic and metabolomics approaches, biological activities, and pharmaceutical mechanisms. We are now in the process of putting together a group of top researchers whose work we would like to feature in this collection, and we would like you to participate.